Simulation of the atmospheric parameters during passage of a tropical storm over the South China Sea: a comparison with MetOcean buoy and ERA‐Interim data. (5th March 2020) - P, Sivaprasad; Samah, Azizan Abu; Babu, C. A; Fang, Yue; Mohd Nor, Mohd Fadzil Firdzaus; Chenoli, Sheeba Nettukandy; Cheah, Wee; Mazuki, Muhammad Yunus Ahmad
Abstract: The accuracy of Weather Research and Forecasting (WRF) model derived meteorological fields during the passage of a tropical storm, Pabuk, over the southern South China Sea is investigated. The European Centre for Medium‐Range Weather Forecasts' ERA‐Interim data were also used for comparison. Data from a MetOcean buoy which captured tropical storm Pabuk were used to evaluate the accuracy of the WRF model. The period of study was from January 1, 2019 to January 5, 2019. Simulated parameters (surface temperature, wind speed and pressure) showed agreement with the buoy data before and after passage of the tropical storm. In contrast, model output shows differences from observations during the passage of the storm near 0600 UTC on January 3, 2019. Overall, surface pressure was simulated with a maximum correlation of 0.93 while the wind speed showed a minimum correlation of 0.76. The surface temperature was simulated with a correlation of 0.78. Weaker correlations arise due to differences in simulated and observed parameters during the storm. During the storm, model estimates overestimated the buoy wind speed and pressure data. The results show the inaccuracy of the simulation due to the vigorous conditions prevailing during the storm. The location of the centre of the storm differing between the model and the ERA‐Interim data could also contribute to the discrepancy of the WRF data. The MetOcean buoy provided a rare opportunity for validation of the WRF model during the storm over the understudied shallow tropical South China Sea. Abstract : A tropical storm is simulated using the Weather Research and Forecasting (WRF) model and surface parameters validated with buoy observations. The WRF model overestimates the surface pressure and wind speed during the passage of tropical storm Pabuk in the South China Sea compared to buoy observations. High resolution simulation could better resolve the horizontal gradient in surface parameters compared to ERA‐Interim data, but the position of the centre of the storm is different in the WRF and ERA‐Interim data.